INTERVIEW WITH GÁBOR ISTVÁN BÍRÓ. - Mullins, Phil (Tradition & Discovery, 2019)
An interview with Gábor István Bíró, who completed his Ph. D. in the Philosophy and History of Science Department (HPS doctoral program) at Budapest University of Technology and Economics (BUTE), which been affiliated with the Michael Polanyi Liberal Philosophical Association (MPLPA), is presented. He mentions his dissertation with a provocative title, "Projecting the Light of Democracy: Michael Polanyi's Efforts to Save Liberalism via an Economics Film, 1933-1948".